Patterns of transhumant livestock system on Mount Zireia, Peloponnese, Greece - Karatassiou M.; Parissi Z.M.; Stergiou A.; Chouvardas D.; Mantzanas K. (Pastoralism and sustainable development: proceedings, 2021)
The transhumant livestock system in Greece, as well as in the Mediterranean basin, is deeply rooted in time, having developed a set of cultural characteristics, the carriers of which continue to be the transhumant farmers. There are more than 3,050 transhumant flocks in Greece, whose major part belongs to Sarakatsans, an ethnic group. These flocks moved on foot in the past, but now most of these movements are carried out with trucks. This study aimed to investigate the dynamic overtime of a) transhumant animals and b) transhumant routes in Mount Zireia in Peloponnese in Southern Greece. The data were taken from personal communications, publications, and data from the Payment and Control Agency for Guidance and Guarantee Community Aid (PCAGGCA). According to the results, a substantial number of transhumant sheep and goats exist in the study area. The traditional routes on foot have stopped, and the animals are currently being moved with trucks, responding to modern socio-economic developments the shared international custom. These changes in the transhumant livestock system probably due to a general trend of transhumant farmers to adopt innovations and modern standards, restrictions in land uses, changes in their living standards.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)